Análise da estabilidade dinâmica do processo de fresamento com ferramenta de topo esférico do aço AISI D6 endurecido - Silva, Fábio Fernandes da (2018)
Molds and dies are used to give a certain shape to a product to be manufactured. In the finishing of this type of tooling the geometry of the tool and the cutting parameters are chosen in order to meet the design requirements related to surface finishing and dimensional accuracy. The ball end mills are recommended for the finishing of inclined surfaces and freeform geometries, this process is characterized by high interruptions during the cut. The time the tool employs in cutting is only a fraction of the tool rotation period. There are variations in the dynamics of the contact between the cutting edge and the surface. This results in different surface finishes and topographical features. In order to verify the influence of these changes on surfaces machined with such tool, eight different cutting trajectory orientations (OTCs) were used such as: upward and downward milling, movement of the tool in horizontal and vertical directions, downmilling and upmilling operation. Inclinations of effective cutting planes of 15, 45 and 75 ° were employed, using the raster milling strategy in a simple direction. AISI D6 steel, thermally treated resulting in 58 HRC, was used in the experiments. The stability evaluation was based on the surface texture with parameters obtained in 3D surface roughness tester (non-contact). Vibrations were captured by a microphone positioned at 20 mm from the tool, in addition to an accelerometer sensor coupled to the spindle head of the machine. When the tool was engaged with the region close to the cutting tip, there was a reduction in RMS vibrations and surface undulations, as well as improvement of the surface finish. The predominant vibrations in this process were those of tooth passage, and when these coincided with 1/3 of the natural vibration frequency of the tool, the surface roughness increased to a depth of cut of 0.3 mm.